A Pragmatic Analysis of Undergraduate Male and Female Students’ Politeness Strategies in Initiating and Terminating Conversations Online - Castro, Jasmine Hannah C.; Duray, Sitti Amina; Tanguihan, Kate Angulie; Syting, Christian Jay O. (Journal Corner of Education, Linguistics, and Literature, 2024)
This study examines the politeness strategies employed by male and female undergraduate students in online interactions, focusing on conversation initiation and termination. A pragmatic analysis was conducted using House and Kasper's (1981) linguistic politeness theory alongside Miles and Huberman's model for data interpretation. The findings indicate that male students predominantly used committers, consultative devices, and downtoners to initiate conversations, while employing downtoners, understaters, and politeness markers for termination. In contrast, female students utilized committers, consultative devices, politeness markers, and playdowns for initiation, and committers, playdowns, and politeness markers for termination. Applying Brown and Levinson's (1987) politeness theory, male students mainly favored positive politeness, negative politeness, and bald-on-record strategies during initiation, while employing both positive and negative strategies for termination. Female students exhibited a preference for positive and negative politeness strategies, along with off-record strategies for initiation, relying solely on positive politeness for termination. These findings highlight distinct gender-specific communication patterns in online environments, providing valuable insights for linguistics, communication studies, and gender studies. The results can guide educators, policymakers, and practitioners in developing inclusive and effective communication strategies tailored to digital learning contexts.